The solar reduction of graphene oxide on a large scale for high density electrochemical energy storage. Issue 10 (29th April 2021) - Yar, Asfand; Dennis, John Ojur; Yasin, Amina; Din, Fasih Ud; Irfan, Muhammad; Khan, Muhammad Saad; Yang, Chun-Chen; Jose, Rajan
Abstract : Graphene oxide can be efficiently reduced on a large-scale using sunlight, and the resulting structure demonstrates superior charge storage properties. Abstract : A green, clean, and rapid process employing sunlight for converting a large quantity of graphene oxide (GO) into reduced graphene oxide (rGO) is presented herein. In this protocol, the sunlight is concentrated using a Fresnel lens and focused on GO, and the heat thus generated reduces GO into rGO within seconds. The reduction process and quality of the Fresnel lens rGO (FrGO) thus produced are examined via thermal, spectroscopic, surface, and microscopic analyses. The electrochemical properties and charge storage parameters of FrGO are analysed using galvanostatic charge–discharge cycling, cyclic voltammetry, and electrochemical impedance spectroscopy using a symmetric electrochemical double layer capacitor in three electrolytes, viz. an alkaline aqueous electrolyte, a neutral aqueous electrolyte, and an ionic liquid. The supercapacitors thus developed delivered specific discharge capacitances of ∼171, 126, and 135 F g −1 at 0.5 A g −1 with potentials of 1.2, 2.0, and 3.4 V, respectively. Owing to the larger potential window and specific capacitance, the devices fabricated using the ionic liquid delivered the highest specific energy ( E S ) and specific power ( P S ). The best-performing device showed an E S value as high as ∼60 W h kg −1 and a P S value as high as ∼6000 W kg −1, thereby demonstrating the feasibility of the process reported herein for practical applications.